2008
DOI: 10.2174/1874354400802010030
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Impulse Control Disorders Among Patients Admitted to a French Psychiatric Emergency Service~!2008-09-16~!2008-11-06~!2008-11-28~!

Abstract: Abstract:Objective: The authors want to examine the prevalence of all impulse control disorders (ICD) among patients examined in a French psychiatric emergency ward and to compare patients with and without ICD.Method: 210 consecutive patients examined in a psychiatric emergency ward were included. We used the Minnesota Impulsive Disorders Interview, a semi-structured clinical interview assessing impulse control disorders (ICD): compulsive buying, trichotillomania, compulsive sexual behavior, kleptomania, pyrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Dittmar [28] have argued that "given that men and women have been shown to differ in their attitudes toward both the Internet and shopping (in conventional environments), it seems surprising that there is little research that explicitly addresses gender differences in on-line buying". A previous study showed high prevalence in compulsive buying in women among patients admitted to a French Psychiatric Emergency Service [29]. Another study which used a random sample, national household telephone survey among 2513 adults from the general population in the US did not find a significant gender effect in their sample [30].…”
Section: Introductionmentioning
confidence: 89%
“…Dittmar [28] have argued that "given that men and women have been shown to differ in their attitudes toward both the Internet and shopping (in conventional environments), it seems surprising that there is little research that explicitly addresses gender differences in on-line buying". A previous study showed high prevalence in compulsive buying in women among patients admitted to a French Psychiatric Emergency Service [29]. Another study which used a random sample, national household telephone survey among 2513 adults from the general population in the US did not find a significant gender effect in their sample [30].…”
Section: Introductionmentioning
confidence: 89%
“…A high level of sensation seeking is present in both dependent and aggressive patients (10). Aggressive behavior is often triggered by heavy drinking or drug intoxication.…”
Section: Introductionmentioning
confidence: 99%
“…Among studies with less direct data, researchers found associations between compulsive buying and nicotine use, and nicotine use and higher intake of alcohol per day, 4 as well as that the first‐degree relatives of compulsive buyers were more likely than controls to suffer from alcohol and/or drug use disorders 5 . We only found one paper with questionable findings, but compulsive buying was grouped with other impulse disorders for analyses 6 . Because of the preceding associations, we hypothesized a relationship between compulsive buying and self‐reported alcohol/drug use in a sample of female outpatients.…”
mentioning
confidence: 75%